Advancements in Structural Testing and Life Predictions of Tidal Turbine Blades (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The structural testing of tidal stream turbines is critical for ensuring their reliability and performance, with testing procedures aligned to standards such as DNVGL-ST-0164 and IEC DTS 62600-3:2020. This research explores the structural integrity of tidal turbine blades, where a set of advanced instrumentation was employed during the testing program, including fibre bragg grating sensors for strain measurement, laser scanning vibrometers for dynamic performance analysis, digital image correlation systems, laser displacement sensors for displacement measurements, and infrared thermal imaging for temperature monitoring. The use of these advanced measuring tools improved the reliability of data collection, post-processing accuracy, and result representation, setting a new standard for structural testing of tidal turbine blades. The case study of ORPC’s 5m long crossflow turbine foil with a rotor diameter of 1.8m, tested under controlled dry laboratory conditions was used. Within this test, an unbalanced rotating mass was used to apply fatigue loading, achieving a groundbreaking milestone of 1.3 million fatigue cycles. This accomplishment represents a significant advancement in fatigue testing techniques. The approach proved more efficient than traditional servo-hydraulic actuators in applying fatigue loads, enabling faster test timelines while maintaining accuracy.Post-test inspections and analyses provided further insights into damage mechanism and material degradation. The damaged sections revealed shear fractures in the matrix materials, bond failures at the matrix-fibre interface, and fibre breakage in both the leading and trailing edges of the turbine foil. Additionally, tensile testing was performed on coupons extracted from undamaged areas of the foil to assess the effects of fatigue degradation. The comparison of strain results from the finite element model with both manufacturer-specified and experimentally derived material properties, using strain distributions identified during the structural testing program, offered valuable insights. This analysis enabled the study to develop a comprehensive understanding of blade performance and material behaviour under the given conditions. Moreover, this study aims to address critical gaps in current structural testing practices, particularly the operational stage impacts often overlooked in dry laboratory conditions and their effects on blade performance. It specifically examines how water absorption impacts the material properties and long-term durability of tidal turbine blades. The research also seeks to identify a methodology for integrating material testing outcomes with the effects of water absorption to develop a predictive framework for estimating blade lifespan in line with the operational status. By incorporating these findings, the industry can accelerate the development of affordable and sustainable tidal energy solutions, contributing to a cleaner and more resilient global energy portfolio.